Can Pediatric Hypertension Criteria Be Simplified?: A Prediction Analysis of Subclinical Cardiovascular Outcomes From the Bogalusa Heart Study. Issue 4 (April 2017) - Xi, Bo; Zhang, Tao; Li, Shengxu; Harville, Emily; Bazzano, Lydia; He, Jiang; Chen, Wei
Abstract : Prehypertension and hypertension in childhood are defined by sex-, age-, and height-specific 90th (or ≥120/80 mm Hg) and 95th percentiles of blood pressure, respectively, by the 2004 Fourth Report. However, these cutoffs are complex and cumbersome for use. This study assessed the performance of a simplified blood pressure definition to predict adult hypertension and subclinical cardiovascular disease. The cohort consisted of 1225 adults (530 men; aged 26.3−47.7 years) from the Bogalusa Heart Study with 27.1-year follow-up since childhood. We used 110/70 and 120/80 mm Hg for children (age, 6–11 years), and 120/80 and 130/85 mm Hg for adolescents (age, 12–17 years) as the simplified definition of childhood prehypertension and hypertension, respectively, to compare with the 2004 Fourth Report (the complex definition). Adult carotid intima-media thickness, pulse wave velocity, and left ventricular mass were measured using digital ultrasound instruments. Compared with normal blood pressure, childhood hypertensives diagnosed by the simplified definition and the complex definition were both at higher risk of adult hypertension with hazard ratio of 3.1 (95% confidence interval, 1.8–5.3) by the simplified definition and 3.2 (2.0–5.0) by the complex definition, high pulse wave velocity with 3.5 (1.7–7.1) and 2.2 (1.2–4.1), high carotid intima-media thickness with 3.1 (1.7–5.6) and 2.0 (1.2–3.6), and left ventricular hypertrophy with 3.4 (1.7–6.8) and 3.0 (1.6–5.6). The results were confirmed by reclassification or receiver operating curve analyses. The simplified childhood blood pressure definition predicts the risk of adult hypertension and subclinical cardiovascular disease equally as the complex definition does, which could be useful for screening hypertensive children to reduce risk of adult cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.